Hexyl gallate for the control of citrus canker caused byXanthomonas citrisubspcitri - Cavalca, Lucia B. [UNESP]; Zamuner, Caio F. C. [UNESP]; Saldanha, Luiz L. [UNESP]; Polaquini, Carlos R. [UNESP]; Regasini, Luis O. [UNESP]; Behlau, Franklin; Ferreira, Henrique [UNESP] (Wiley-Blackwell, 2020)
Brazil is the biggest producer of sweet oranges and the main exporter of concentrated orange juice in the world. Among the diseases that affect citriculture, Asiatic citrus canker, caused by the bacterial pathogen Xanthomonas citri, represents one of the most significant threats. The current Brazilian legislation regulating the control of citrus canker no longer requires the eradication of affected trees in states where the incidence of the disease is high. Instead, control involves disease control measures, including periodic preventative spraying of copper compounds. The long-term use of copper for plant disease control has raised concerns about environmental accumulation and toxicity, as well as the selective pressure it exerts leading to the emergence of copper-resistant X. citri strains. Here, we evaluated hexyl gallate (G6) as an alternative to copper compounds for citrus plant protection. G6 was able to protect citrus nursery trees against X. citri infection. Thirty days after inoculation, the trees treated with G6 developed 0.5 lesions/cm(2)leaf area compared with the 2.84 lesions/cm(2)observed in the untreated control trees. Also, G6 did not interfere with germination and root development of tomato, lettuce, and arugula, which is consistent with our previous data showing that G6 is safe for tissue culture cell lines. Membrane permeability tests showed that the primary target of G6 is the bacterial outer membrane. Finally, we could not isolate spontaneous X. citri mutants resistant to G6 nor induce resistance to G6 after long-term exposures to increasing concentrations of the compound, which suggests that G6 may have multiple cellular targets. This study demonstrated that G6 is a promising candidate for the development and use in citrus canker management.
Keywords: citrus protection; copper alternative; ester of gallic acid; sustainable agriculture